Screencast Feedback for Essays on a Distance Learning MA in Professional Communication - Edwards, Kirstie; Dujardin, Anne-Florence; Williams, Noel (Journal of Academic Writing, 2012)
This action research explored the potential of audio-visual screencasting for assignment feedback on a distance learning (DL) course. A screencast is a combination of voice recording and screen capture, which can be played in any browser, like a video. Here it is used to capture a tutor’s editing and highlighting activities in a document, whilst simultaneously recording spoken feedback. Research suggests that audio-visual feedback may resolve some of the current problems with written feedback. A pilot study is reported which trialled screencasting for essay feedback on a master's level DL module at Sheffield Hallam University. Fourteen students participated and were randomly divided between two groups to receive either written or screencast feedback first. After receiving the first feedback type, students completed a short questionnaire online. The second type of feedback was then distributed to the students, who completed the same questionnaire for the second type of feedback. The results suggest that feedback is received more positively in the richer media of audio-visual screencasting and that this may encourage emotions more conducive to receiving and processing feedback and help to socialise students within the learning context by giving them a sense of belonging to the community. Simultaneous visual cues and explanations appear to help with understanding, and it is quicker to capture screencasts than it is to write feedback. However, preferences for written feedback were related to the holistic overview of a document, which could be scanned and revisited, and which was not confined to a linear delivery, nor time-limited. Audio-visual screencasting will therefore only be adopted for formative feedback during modules, and will be structured with spoken overviews.